Relationship between triglyceride HDL-cholesterol ratio and severity of coronary artery disease in patient with acute coronary syndrome (Bangladesh Medical Journal, 2016)
Cardiovascular Disease (CVD) is the leading cause of death worldwide, responsible for one third of death. Coronary artery Disease (CAD) is the most common cause. Dyslipidaemia is one of the major contributors of increased CAD risk. High LDL-C, high TG and low HDL-C have all been as predictors for CAD risk. TG/HDL-C ratio could be a very important, easy, non-invasive means of predicting the presence and extent of coronary atherosclerosis. The aim of this study was to evaluate the association between TG/HDL-C ratio and the extent of CAD assessed by coronary angiogram in our setting. This cross sectional analytical study has been done in the Department of Cardiology, Sir Salimullah Medical College & Mitford Hospital. A total 118 patients with newly diagnosed ACS, undergoing coronary angiogram in were selected purposively. Previous history of PCI or CABG, patients getting lipid lowering drugs, patient with congenital heart disease or vulvular heart disease was excluded. Angiographic severity of coronary artery disease was assessed by 2 indices vessels score and Lesion score. Smoking was found in highest percentage (65.3%) and half of the patients risk factor were hypertension (51.7%) and overweight (50.8%). The relationship between vessel score with TG/HDL-C ratio shows that among patients with triple vessel disease on coronary angiogram, 93% had high (?4) TG/HDL-C ratio whereas among double vessel disease patients, 82% patients had high (?4) TG/HDL-C ratio. The 157 association between atherosclerosis lesion score with TG/HDL-C ratio shows that with the increase level atherosclerosis TG/HDL-C ratio also increased. A subject with low HDL (4) was found with severity of CAD in relation to vessel score and atherosclerosis lesion score. High TG/HDL-C ratio indicates an atherogenic plaque and a significant risk for the development of coronary artery disease. In this study high TG/HDL-C ratio was found as the most powerful predictor of coronary heart disease among all the lipid variables examined. This finding can help us to find out high risk ACS patient and plan for treatment strategy of severe CAD in our population.Bangladesh Med J. 2014 Sep; 43 (3): 157-161